SingHealth Cyber Attack : Learning from COI Findings - Jayakumar, Shashi (2019)
How do we protect our critical information infrastructure from evolving threats? What steps do we need to take to prepare for future adversaries who are continually refining their methods? How can these steps be applied to the health sector?